2017
DOI: 10.1016/j.ejpn.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

How does the interaction of presumed timing, location and extent of the underlying brain lesion relate to upper limb function in children with unilateral cerebral palsy?

Abstract: Background: Upper limb (UL) function in children with unilateral cerebral palsy (CP) may vary largely depending on presumed timing, location and extent of brain lesions. These factors might exhibit a complex interaction and the combined prognostic value warrants further investigation. This study aimed to map lesion location and extent and assess whether these differ according to presumed lesion timing and to determine the impact of structural brain damage on UL function within different lesion timing groups. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 44 publications
6
38
0
Order By: Relevance
“…It was observed that AHA and MUUL scores between children with unilateral and bilateral brain injury were not statistically significantly different (Table ), despite lesions being more severe based on the semi‐quantitative scoring. This result is consistent with previous findings that the presence of unilateral or bilateral damage had no predictive value on hand performance (Holmefur et al, ; Mailleux et al, ). Furthermore, bilateral brain injury being thought to have a protective effect with respect to brain reorganization, by preventing reorganization towards the dominant hemisphere that is known to lead to poorer functional outcomes (Eyre et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…It was observed that AHA and MUUL scores between children with unilateral and bilateral brain injury were not statistically significantly different (Table ), despite lesions being more severe based on the semi‐quantitative scoring. This result is consistent with previous findings that the presence of unilateral or bilateral damage had no predictive value on hand performance (Holmefur et al, ; Mailleux et al, ). Furthermore, bilateral brain injury being thought to have a protective effect with respect to brain reorganization, by preventing reorganization towards the dominant hemisphere that is known to lead to poorer functional outcomes (Eyre et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…The timing of the lesion during gestation is closely related to the type of the damaged tissue and can be classified into three categories: malformations (1 st and 2 nd trimesters of pregnancy), periventricular lesion (PV, early 3 rd trimester), and corticosubcortical lesions (CSC, late 3 rd trimester and around birth) [ 7 ]. Previous studies investigating the impact of lesion timing on UL function have shown that individuals with a later lesion (i.e., CSC lesions) present with poorer UL motor and sensory functions [ 2 , 3 , 5 ]. Besides lesion timing, lesion location and extent have shown to play an important role in determining UL function, whereby damage to the posterior limb of the internal capsule (PLIC) and the basal ganglia, and a larger lesion extent is related to worse UL motor and sensory functions [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigating the impact of lesion timing on UL function have shown that individuals with a later lesion (i.e., CSC lesions) present with poorer UL motor and sensory functions [ 2 , 3 , 5 ]. Besides lesion timing, lesion location and extent have shown to play an important role in determining UL function, whereby damage to the posterior limb of the internal capsule (PLIC) and the basal ganglia, and a larger lesion extent is related to worse UL motor and sensory functions [ 2 , 3 ]. However, there is still large variability in UL function that remains unexplained based on these factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, mirror movements have a negative impact on UL function [21][22][23], yet their value to influence treatment response remains unknown. Among potential neurological factors are the underlying lesion type (predominantly white matter vs. grey matter damage) and the corticospinal tract (CST) wiring pattern, due to their value in explaining variability in UL function [24][25][26]. Thus far, only one small study showed improvements after CIMT regardless of the lesion type [27].…”
Section: Introductionmentioning
confidence: 99%